2017
DOI: 10.1136/jclinpath-2016-204271
|View full text |Cite
|
Sign up to set email alerts
|

Acute presentation of autoimmune hepatitis: a multicentre study with detailed histological evaluation in a large cohort of patients

Abstract: The acute presentation of AIH represents the entire histological spectrum of acute hepatitis and chronic hepatitis with various activity grades and fibrosis stages that clinically correspond to acute-onset AIH and acute exacerbation of classic AIH, respectively. Although there are no pathognomonic features for the pathological diagnosis, the prominent presence of lobular and perivenular necroinflammatory activity, pigmented macrophages and cobblestone appearance of hepatocytes in addition to the classic AIH fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 74 publications
6
53
0
Order By: Relevance
“…In our model of TCE‐induced AIH, immune cells infiltrate the liver leading to a cascade of inflammatory events that are counter‐balanced by an increase in interleukin (IL)‐6‐related signaling molecules that are important in liver regeneration and repair (Gilbert et al, ). Similar findings have been reported idiopathic AIH in humans (Nguyen Canh et al, ). The bi‐directional interaction between the gut and liver has been documented.…”
Section: Introductionsupporting
confidence: 90%
“…In our model of TCE‐induced AIH, immune cells infiltrate the liver leading to a cascade of inflammatory events that are counter‐balanced by an increase in interleukin (IL)‐6‐related signaling molecules that are important in liver regeneration and repair (Gilbert et al, ). Similar findings have been reported idiopathic AIH in humans (Nguyen Canh et al, ). The bi‐directional interaction between the gut and liver has been documented.…”
Section: Introductionsupporting
confidence: 90%
“…The severity of each pathological finding varies among individual cases. Among these features, prominent lobular and perivenular necroinflammatory activity, pigmented macrophages, cobblestone appearance of hepatocytes, plasma cell infiltration, and emperipolesis are useful for the pathological diagnosis of AIH with acute presentation . Moreover, plasma cell infiltration could be a diagnostic requirement for AIH with acute presentation as previous reports and our present survey have revealed plasma cell infiltration in over 80% of biopsy samples …”
Section: Autoimmune Hepatitis With Acute Presentationsupporting
confidence: 67%
“…37,38 Alternatively, the histogenesis of CN in AIH with acute presentation is not related to the autoimmune process. 44 According to our survey of Japanese patients, 45 the histological features of AIH with acute presentation include several that overlap with those of classical AIH: (i) lobular (parenchymal) changes including CN (collapse and lytic type), centrilobular congestion/hemorrhage, centrilobular endothelial cell injury/central vein endothelitis, cobblestone appearance of hepatocytes, pigmented macrophages, and centrilobular fibrosis; and (ii) portal/periportal changes, including portal inflammation, interface hepatitis, portal plasma cell infiltration, hepatic rosette formation in periportal areas, bile duct injury, and portal/periportal fibrosis. The severity of each pathological finding varies among individual cases.…”
Section: Histology Of Aih With Acute Presentationmentioning
confidence: 99%
“…35 In another recent retrospective histological evaluation of 87 Japanese patients with acute AIH, it was shown that, in accordance with the US-ALFSG findings, 3 the patients had prominent lobular and perivenular necroinflammation (including centrilobular necrosis), pigmented macrophages, and cobblestone appearance of hepatocytes along with typical AIH features, like plasma cell infiltration and emperipolesis. 38 All 34 AS-AIH patients were promptly treated within 7-10 days after the onset of symptoms. Of note, the patients had a median INR of 1.52, which shows that they were not "too sick" and that treatment was initiated promptly enough in order to interrupt the catastrophic process and prevent deterioration of liver function and ALF development.…”
Section: Figurementioning
confidence: 99%